164k views
4 votes
10. Use the Distributive Property to solve the
equat on 3(x- 6) + 6 = 5x - 6

2 Answers

2 votes

Answer:

x=-9

Explanation:

3x-18+6=5x-6 distribute

3x-18=5x cancel out 6es

-18=2x subtract 3x

x=-9 divide by 2

Hope this helps plz hit the crown:D

User Moise
by
6.0k points
3 votes

Answer:

x = -3

Explanation:

3(x - 6) + 6 = 5x - 6

Distribute;

3x - 18 + 6 = 5x - 6

3x - 12 = 5x - 6

Subtract 5x from both sides;

-2x - 12 = -6

Add 12 to both sides;

-2x = 6

Divide both sides by -2

x = -3

User JPWilson
by
5.8k points